Involvement of Students in Experimental In-store Research Projects - Pethő, Beata (European Scientific Journal, ESJ, 2016)
In the field of business education, the issue of how many practical skills we can teach students and in what way we can do this has been an ongoing problem. In our modern world, it is essential for students to adopt a ‘learning by doing’ attitude as early as their undergraduate years and enter the labour market having useful insights into business. It is of particular significance for students in business sectors to understand the practical considerations of methodology, as a result, they should be involved in the research practices of the branch of science they have chosen to study. The aim of this research, besides supporting the practice of business education, is to explore how to describe consumer behaviour in in-store situations. Therefore, this paper is composed of two parts: one of them describes the background and methods of the research project, while the other presents an applied business education case.